De Quervain's Tenosynovitis and Thumb Pain in Physiotherapists Practicing Manual Therapy: Prevalence and Associated Factors - Saba Riaz; Tooba Mazhar; Sumbal Riaz; Ayesha Batool; Awishbah Khan; Sadia Khan (BioMedica, 2023)
Background and Objective: Manual therapy is a treatment approach by physical therapists where different techniques are applied to patients with hands for rehabilitation purposes. The objective of the study was to find the frequency of De’Quervain tenosynovitis and thumb and wrist pain in physical therapists working in different rehabilitation centers in relation to age, body mass index (BMI), and working hours. Methods: A cross-sectional study was conducted on 135 physical therapists working in different settings in Lahore, Pakistan. Physiotherapists were enrolled by convenience sampling. Data were recorded on a questionnaire form. Finkelstein test was performed to check De Quervain’s tenosynovitis. A numeric pain rating scale was sued to measure pain. The data were tested for significance using statistical tests. Results: On the dominant hand, 99 (73.3%) physical therapists had no wrist pain, 104 (77%) had no thumb pain, 28 (20.7%) had mild wrist pain and 20 (14.8%) had mild thumb pain. Only 21 (15.6%) physiotherapists were tested positive for Finkelstein (De Quervain’s tenosynovitis). Finkelstein test reported 100% negative result on the non-dominant side. There is a negative correlation between thumb pain with the age (r = -0.005), BMI (r = -0.110) and working hours (r = -0.033) of the physical therapists. Conclusion: The study concluded that the prevalence of De Quervain’s tenosynovitis, thumb, and wrist pain was more on the dominant hand than on the non-dominant side. The majority of the physical therapists reported mild to no pain in the wrist and thumb. There is a negative correlation of thumb pain with age, BMI and working hours.